Validity and Reliability of A Battery of Combined Tests for Assessing Perceptual-Motor Decision-Making Speed in Football - Ammar Faris Atiyah (Program Studi Pendidikan Kepelatihan Olahraga, 2026)
The ability to process visual stimuli and make precise motor decisions within a few milliseconds is an essential component of high-level performance in football. Despite considerable theoretical interest, there is no psychometrically validated test battery available to comprehensively assess perceptual-motor decision-making speed (PMDS) in top Iraqi footballers. Objective: The aim of this study was to develop a test battery comprising five PMDS tests and to determine its content validity, construct validity, criterion-related validity and test-retest reliability among footballers in the Iraqi Premier League. A three-phase sequential mixed-methods design was employed. In Phase 1, content validity was determined by a panel of experts (n = 12) using Lawshe’s content validity ratio (CVR). During phase 2, test-retest reliability was assessed in 30 players during two sessions 72 hours apart using intraclass correlation coefficients (ICC₂,₁), standard error of measurement (SEM) and the minimum detectable change (MDC₉₅). During phase 3, conceptual validity (known groups: elite versus sub-elite, n = 75) and criterion-related validity were assessed using a game performance index (n = 75). The test battery comprised five sequential tests: simple reaction time, choice reaction time, anticipation time, decision-making under dual-task conditions, and a game-based decision-making task. Results, all twelve items assessing content validity exceeded the minimum CVR threshold of 0.83 (range: 0.85–0.96). The ICC values ranged from 0.89 to 0.94, indicating excellent test-retest reliability. The SEM values ranged from 12.4 to 21.3 ms. Elite players achieved significantly faster PMDS scores than non-elite players in all five tests (p < 0.001, d = 0.84–1.12). The total score of the test battery was significantly correlated with the match performance index (r = −0.68, p < 0.001). Confirmatory factor analysis confirmed a unidimensional structure (CFI = 0.96, RMSEA = 0.048). Conclusions, The complete PMDS battery exhibits robust psychometric properties and is suitable for talent identification, performance monitoring and applied research among Iraqi Premier League footballers as well as comparable elite populations.